Back Cover: Localized states emission in type‐I GaAsSb/AlGaAs multiple quantum wells grown by molecular beam epitaxy (Phys. Status Solidi RRL 3/2017). Issue 3 (March 2017) - Ge, Xiaotian; Wang, Dengkui; Gao, Xian; Fang, Xuan; Niu, Shouzhu; Gao, Hongyi; Tang, Jilong; Wang, Xiaohua; Wei, Zhipeng; Chen, Rui
Abstract : No abstract is available for this article. Abstract : Localized centers in multiple quantum wells (MQWs) can easily trap free carriers and produce localized states. Localized states expand the conduction‐ and valance‐band edges and lead to a tail of the density of states. It greatly affects the optical properties as well as the carrier dynamics. Xiaotian Ge et al. (article no. 1700001 ) present a comprehensive study of the properties of localized states in the GaAsSb/AlGaAs MQWs system. It is helpful for the practical application of GaAsSb‐based MQW devices. In this paper, GaAs0.92 Sb0.08 /Al0.2 Ga0.8 As MQWs were grown by molecular beam epitaxy and their optical properties were investigated by temperature‐dependent and excitation power‐dependent photoluminescence (PL) measurements. The localized states emission was observed at low temperature. The peak on the low‐energy side of the PL spectra was confirmed as localized states emission by a long tail and the high‐energy side peak was confirmed to be free‐carrier emission by the temperature‐dependent emission peak position. The localized states emission peak exhibited a blueshift with increasing excitation power, which was attributed to the localized states filling effect.